Induced Arp2/3 Complex Depletion Increases FMNL2/3 Formin Expression and Filopodia Formation - Dimchev, Vanessa; Lahmann, Ines; Koestler, Stefan A.; Kage, Frieda; Dimchev, Georgi; Steffen, Anika; Stradal, Theresia E. B.; Vauti, Franz; Arnold, Hans-Henning; Rottner, Klemens (Frontiers in Cell and Developmental Biology, 2021)
The Arp2/3 complex generates branched actin filament networks operating in cell edge protrusion and vesicle trafficking. Here we employ a conditional knockout mouse model permitting tissue- or cell-type specific deletion of the murine Actr3 gene (encoding Arp3). A functional Actr3 gene appeared essential for fibroblast viability and growth. Thus, we developed cell lines for exploring the consequences of acute, tamoxifen-induced Actr3 deletion causing near-complete loss of functional Arp/3 complex expression as well as abolished lamellipodia formation and membrane ruffling, as expected. Interestingly, Arp3-depleted cells displayed enhanced rather than reduced cell spreading, employing numerous filopodia, and showed little defects in the rates of random cell migration. However, both exploration of new space by individual cells and collective migration were clearly compromised by the incapability to efficiently maintain directionality of migration, while the principal ability to chemotax was only moderately affected. Examination of actin remodelling at the cell periphery revealed reduced actin turnover rates in Arp2/3-deficient cells, clearly deviating from previous sequestration approaches. Most surprisingly, induced removal of Arp2/3 complexes reproducibly increased FMNL formin expression, which correlated with the explosive induction of filopodia formation. Our results thus highlight both direct and indirect effects of acute Arp2/3 complex removal on actin cytoskeleton regulation.